ANALISIS EFEKTIVITAS PEMBELAJARAN BERBASIS MICROLEARNING DALAM MENTRANSFORMASI KETERAMPILAN ABAD 21: KAJIAN PUSTAKA - Risandy Madu; Gesika Avelina; Rendy .S. Sambara (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
The development of digital technology has made learning faster, more flexible, and more aligned with the needs of 21st-century skills, such as microlearning. Microlearning is the presentation of material in bite-sized, flexible formats that are easily accessible through digital devices. This model emerged in response to changes in technological development. Therefore, the purpose of this study was to evaluate the features and effectiveness of microlearning and its role in transforming 21st-century skills, namely critical thinking, creativity, collaboration, communication, and digital literacy. A review of books, journals, research reports, and related scientific sources was used as the library research method. The results showed that microlearning is effective in improving student comprehension, retention, motivation, and engagement. This is due to the fact that it presents material in a straightforward and straightforward manner. Furthermore, it is evident that microlearning plays a significant role in the development of the 4Cs: fostering rapid analytical skills in...